Genetics-Based Technologies for Sustainable Development in Philippine Aquaculture: The Case of Tilapia - Ruben C. Sevilleja (Blackwell Publishing, 2025)
The need for appropriate tilapia technologies to enhance aquaculture development in the Philippines has been demonstrated with regard to the relevance and availability of highly productive technologies such as genetic manipulation. With the availability of genetics-based technologies, opportunities for farmers to raise the productivity of their resources take on a special importance. These technologies are vital to aquaculture in terms of productivity, stability, and sustainability. The importance of genetics-based technologies in aquaculture is aptly illustrated by the successes gained by the Philippine tilapia industry. Constraints, however, imposed by shortages of land, capital, and other resources, limit the rate of investment and the extent to which genetics-based technologies replace existing methods of production, which, in turn, deters the further development of tilapia culture in the country. At the same time shrinking investments in public goods, growing private sector activities and participation, and changing legal and regulatory regimes, which, in turn, are affecting genetics-based aquaculture and exerting pressure for change, accompany such development. Moreover, the application and dissemination of these technologies and their products present formidable challenges and complications, foremost of which are issues and concerns surrounding environmental biosafety and the management and ownership of intellectual property. This paper provides an overview of the development and adoption of genetics-based technologies for aquaculture of tilapia, highlighting the policy environments that led to the current dynamism of the tilapia industry in the Philippines.